CONVECTIVE-CONDENSATION METHOD OF DRYING HEAT-SENSITIVE MATERIALS - Sorokovaya, N.; Snezhkin, Y.; Shapar, R. (Енергетика і автоматика, 2016)
This paper  a method for dehydrating heat-sensitive materials in the co-current belt dryer , which includes changes in temperature and moisture content of the drying agent and allowing to reduce the drying time and to ensure energy and resource conservation is presenting. The mathematical model and a numerical method for calculating the dynamics of heat and mass transfer, phase transformations and shrinkage during drying of colloidal capillary-porous bodies in a co-current belt dryer are presented.